Non-Tariff Barriers in services trade, Foreign Direct Investment and international trade - (:unkn) unknown (My University, 2022)
This thesis studies the effects of Non-Tariff Barriers (NTBs) to trade in services on international trade. It contributes to the empirical analysis of the effects of sectoral restrictions in services trade on world trade. In the first chapter, we empirically examine the impacts of NTBs in services and regulatory disparity (transport, logistics, distribution, financial and business) on food trade among OECD countries. The results suggest negative effects of sectoral restrictions except in the distribution sector on trade in food products. However, the regulatory disparity between countries has a significant negative impact on food trade. This impact decreases when the exportercountry is closed to service providers. In the second chapter, we empirically analyze the impacts of FDI restrictions on cross-border investment between advanced (OECD) and emerging countries. We conclude that restrictions in the services sector of FDI impede cross-border investment across advanced and emerging countries. Furthermore, restrictions in the services sector hinder cross border investment between advanced countries and restrictions in the primary, manufacturing and natural resources sector hamper inward FDI in emerging countries. In the last chapter, we use a theoretical model to study the gains of services liberalization on intra-African trade in the context of the African Continental Free Trade Area (AfCFTA). The results show positive effects of services liberalization on GDP growth, income, welfare and intra-African trade, particularly trade in manufacturing goods and natural resources. The AfCFTA agreement creates both long-term trade creation and diversion, but the welfare gain is still positive and significant over the long term in Africa.
Keywords: African Research